Auditory Processes in Stutterers - GREGORY, HUGO H.; MANGAN, JAMES (Speech and Language, 1982)
This chapter presents the studies carried out to investigate the functioning of the auditory system in stutterers. Additionally, relates auditory processes to motor control factors in stutterers. Speculations about the masking effect in ameliorating stuttering, the impact of delayed auditory feedback (DAF) on normal speech, and the way in which DAF affects the speech of stutterers has led to much research focusing on the functional integrity of peripheral and central auditory feedback processes in stutterers and nonstutterers. The chapter discusses the evoked response audiometry (ERA) to evaluate the integrity of the auditory system at various levels and describes the measurement of averaged electroencephalographic response (AER). It is expected that a steady increase in the use of AER techniques in the study of auditory processes related to speech and language and speech and language disorders including stuttering. With patience and care, these techniques can be used with children in cases where it may not be possible to utilize procedures requiring behavioral responses; the conscious control of the subject is not required. Although a bit uncomfortable, this technique is not invasive